Juridical Analysis of Settlement of Criminal Excise Cases Using The Principles of Restorative Justice - Iswan Heru Widarto (International Journal of Social Service and Research, 2023)
The enforcement of criminal law in the Excise Law traditionally focuses on penalties. Still, since Law Number 7 of 2021, PPNS Customs and Excise investigators at the Cikarang Customs and Excise Office can now apply the principle of restorative justice in resolving criminal excise cases. This research, conducted through normative legal methods with a case approach, aims to clarify the concept and mechanism of implementing restorative justice in resolving excise criminal cases at the Cikarang Customs and Excise Office. Results from September 2023 reveal that the office has successfully implemented restorative justice 106 times, leading to asset recovery of Rp. 2,434,494,100. The benefits include a decrease in excise violations, with only a 1.9% recidivism rate. In conclusion, restorative justice has been effective, prioritising beneficial justice efforts and increasing state revenue while deterring repeat excise criminal acts.